SOSIAL EKONOMI KELUARGA DAN HUBUNGANNYA DENGAN KENAKALAN REMAJA DI DESA LANTASAN BARU KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - CRISTEDI PERMANA BARUS (Welfare StatE, 2013)
Adolescence is the transition from childhood to adulthood that adolescents are very vulnerable to psychosocial problems is the trigger juvenile (Juvenile deliquency). Juvenile delinquency can be attributed to the possible influence of socio-economic families. From some of the theories and research results show that there is a relationship between socio-economic conditions with the emergence of acts of delinquency by juveniles. According to Santrock juvenile delinquency is more common in lower socioeconomic groups, while according to Hurwitz adolescents from higher socioeconomic groups are also likely to commit acts of delinquency. This thesis is titled Family Social Economic and In Relation to Adolescent Delinquency In Lantasan Baru Village Sub-District of Patumbak Regency of Deli Serdang. the study used the descriptive type depict or describe an object or phenomenon under study. Sampling was done by using simple random sampling with a sample of 42 respondents. The data that has been collected analyzed by an interpretation of the data obtained, whether through questionnaires and interviews with the respondents so as to draw conclusions on research problems. The results showed that adolescents in the village of Lantasan Baru come from different socio-economic levels of families, ranging from higher socioeconomic families to low socio-economic families. Types of juvenile deliquency condcted such diverse adolescents of low sosioeconomic mischhief such as fighting, steealing, skipping school, watching porn and others, adolescents from middle socioeconomic like fighting, skipping school, gambling, smoking, stealing at home, racing, while adolescents from high socioeconomics mischef such as gambling, drinking, having sex , taking drugs and others. By analyzing data from the respondent get concluded that socioeconomic families have partnerships with the rampant acts of juvenile delinquency in the village of Lantasan Baru Patumbak district Deli Serdang regency. Keywords: Socioeconomic and Adolescent Delinquency